Sistem Informasi Pengelolaan Kas Kecil Pendapatan Barang Masuk dan Keluar pada PT. Universal Carpet and Rugs Berbasis Web - Fani Eli Zebua; Bernadus Gunawan Sudarsono; Sharyanto Sharyanto (FIKOM - Bung Karno University, 2023)
PT. Universal Carpet and Rugs is a company engaged in the carpet textile industry. This company carries out quite a lot of transactions involving petty cash in its company activities and until now the process of managing petty cash is still carried out manually by the finance department by recording every petty cash transaction which causes frequent data loss or human errors which can cause losses. on the company. From the description of the problems that occurred, a Web-Based Petty Cash Management Information System was designed and built at PT. Universal Carpet and Rugs with a proposed budget request process, budget realization process and budget realization data collection process added from an analysis of the system that is already running and is expected to be able solve existing problems. The methods used in completing this final project are observation methods, interview methods, and literature study methods. While the system modeling uses the Unified Modeling Language (UML) method using the PHP programming language, while the software / tools used are MySQL as the database. This Petty Cash Information System can be a solution that can be used to work on the cash management process that runs at PT. Universal Carpet and Rugs.